Balancing Publication Incentives and Downstream Research at State Islamic University of North Sumatra Medan for Regional Independence - Darwis (AMUYA: JOURNAL OF MANAGEMENT, 2026)
This Policy Paper provides an overview of the main policy studied, namely the low synergy of research programs at UIN Sumatera Utara Medan based on community and industry needs, which directly hampers the effectiveness and impact of research outputs. This problem is rooted in three policy factors: 1) research orientation gap; 2) lecturer evaluation system that prioritizes journal publication; and 3) national regulatory pressure and institutional accreditation targets. This failure of synergy is caused by perverse policy incentives, where lecturers rationally choose quickly measurable outputs (publications) over impactful outputs (downstream), a phenomenon reinforced by metrics fixation and relevance-rigour trade-off. This study uses a descriptive qualitative method with a policy analysis approach. Data were collected through a study of statutory regulatory documents (UU, PMA) and technical guidelines at UIN Sumatera Utara Medan, reinforced by theoretical and conceptual literature studies (triple helix model, principal-agent theory, and user-centric research). The evaluation of alternative policies was conducted comparatively using William N. Dunn scoring analysis based on the criteria of effectiveness, efficiency, adequacy, equity, and responsiveness. Dunn's analysis identified that mandatory stakeholder engagement in research proposals is a highly effective and responsive alternative. Therefore, it is recommended that the Rector of UIN Sumatera Utara Medan issue a Rector's Decree requiring evidence of stakeholder engagement (community or industry) in every internally funded research proposal. This recommendation aims to address the root cause of distorted incentives by forcing a shift in research behavior from a publish-only focus to demand-driven and impact-oriented research.